Response of Two Chickpea (Cicer arietinum L.) Varieties to Rates of Blended Fertilizer and Row Spacing at Tselemti District, Northern Ethiopia - Tesfahun Mekuanint; Yemane Tsehaye; Yemane G. Egziabher (Advances in Agriculture)
Effects of row spacing, blended fertilizer rates, and varieties on some agronomic traits of chickpea were evaluated with the objective of investigating response of Kabuli and Desi type chick pea varieties to blended fertilizers rates and interrow spacing. The study was done using split plot design interrow spacing as a main plot, and fertilizer and variety as a subplot, where three row spacings (20 cm, 30 cm, and 40 cm) were assigned to the main plot while the factorial combination of four blended (NPSB) fertilizer rates (0 kg/ha, 50 kg/ha, 100 kg/ha, and 150 kg/ha) and representative of Kabuli and Desi type chickpea varieties such as Arerti and Mariye, respectively, were assigned to the subplot. Main effect of interrow spacing did not show significant difference on many studied agronomic parameters. Similarly, main effect of blended fertilizer rates and varieties did not reveal a significant difference for the studied parameters. However, significant differences were obtained on phenology, yield components, and yield for the varieties. Blended fertilizer rates utilized in Tselemti District did not show differences in most of studied traits. Reasonable row spacing of 20 cm for both types of chickpea could be used for the studied area.